1990
DOI: 10.1073/pnas.87.3.968
|View full text |Cite
|
Sign up to set email alerts
|

Prevention of diabetes in nonobese diabetic mice by tumor necrosis factor (TNF): similarities between TNF-alpha and interleukin 1.

Abstract: The role of tumor necrosis factor a (TNF-a) in the pathogenesis of autoimmune diabetes mellitus was tested in the nonobese mouse (NOD) model system. The effects of TNF-a were assessed on three levels: (i) insulitis development, (ii) development of overt diabetes, (iii) adoptive transfer of diabetes by splenic lymphocytes. Spontaneous diabetes mellitus was blocked in NOD mice by long-term treatment with recombinant TNF-a. Treatment with TNF-a caused'a significant reduction in the lymphocytic infiltration associ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

17
171
1
5

Year Published

1991
1991
2009
2009

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 308 publications
(194 citation statements)
references
References 30 publications
17
171
1
5
Order By: Relevance
“…Our present results are consistent with our earlier experience with IL-1Ra in a chemically induced IDDM model [8]. In contrast, Jacob et al found that systemic administration of tumour necrosis factor-alpha (TNF-a) and IL-1 protects NOD mice from developing insulitis [4]. However, studies in which cytokines are systemically administered may not be optimal for demonstration of their role in organspecific disorders like IDDM.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…Our present results are consistent with our earlier experience with IL-1Ra in a chemically induced IDDM model [8]. In contrast, Jacob et al found that systemic administration of tumour necrosis factor-alpha (TNF-a) and IL-1 protects NOD mice from developing insulitis [4]. However, studies in which cytokines are systemically administered may not be optimal for demonstration of their role in organspecific disorders like IDDM.…”
Section: Discussionsupporting
confidence: 90%
“…In the inbred NOD mouse, a commonly used experimental model for IDDM, allogeneic transplanted pancreatic islets are reported to be rapidly destroyed by disease recurrence in contrast to allogeneic transplanted pituitary glands [2]. Several molecular/cellular mechanisms for this graft damage have been suggested, including involvement of the proinflammatory cytokines IL-1 and interferon-gamma (IFN-g) [4][5][6]. In the present study, the role of IL-1 in this process was investigated by using an IL-1 receptor antagonist (IL-1Ra) as a potential inhibitor of the diabetogenic process, after syngeneic pancreatic transplantation, in NOD mice.…”
Section: Introductionmentioning
confidence: 99%
“…In particular, the expansion of antigen-experienced T cells was prolonged in TNF À/À mice and, in contrast to wtTNF mice, EAE was readily induced by a second administration of myelin oligodendrocyte glycoprotein peptide [25]. In a spontaneous mouse model of insulin-dependent diabetes mellitus, the NOD mouse, TNF led to increased [26,27] or attenuated [28][29][30] islet infiltration, depending on timing and duration of exposure of the immune system to TNF [11]. Indications for an immunoregulatory role for TNF have been also reported in mouse models of infectious diseases, such as in schistosome [31] and M. tuberculosis/BCG infections [32], where TNF was found to be required to limit immunopathologies in the liver and lung, respectively.…”
Section: Discussionmentioning
confidence: 99%
“…However, the role of TNF-α in Type 1 diabetes is still controversial. Previous studies in animal models for Type 1 diabetes have clearly demonstrated that TNF-α could participate in the development of diabetes, while other studies have highlighted the role of TNF-α in silencing the autoimmune process, suggesting a dual role of TNF-α in the development of the disease based on the timing of TNF-α expression [47,48,49,50,51,52,53].…”
Section: Discussionmentioning
confidence: 99%